The role of emergency medicine interest groups in the development of emergency medicine: A case of Mbarara University of Science and Technology—Emergency Medicine Interest Group (MUST-EMIG) in Uganda - Kajjimu, Jonathan; Odakha, Justine Athieno; Makai, Conrad; Kaginda, Beneth Tusiime; Nakachwa, Janat; Karungi, Annet; Lubega, Frank; Tukamuwebwa, Jespa; Kakande, Reagan; Lyon, Mary Ellen; Tagg, Andrew (African Journal of Emergency Medicine, 2023)
Introduction: Emergency medicine (EM) is a new specialty in Uganda. There is no current formal EM undergraduate curriculum. The Mbarara University of Science and Technology Emergency Medicine Interest Group (MUST-EMIG) was established to bridge this gap. This survey was done to assess the contributions of MUST-EMIG. Objectives of the study were to: discover students’ reasons for joining the MUST-EMIG; assess whether interest in learning emergency medicine was affected by participation in MUST-EMIG; evaluate plans to pursue emergency medicine as a specialty before and after joining MUST-EMIG; determine whether MUST-EMIG affected students’ perception of emergency medicine’s importance in Uganda’s health care system; and elicit feedback from students on their experience as members of MUST-EMIG. Methods: The MUST-EMIG executive developed a membership survey which was reviewed by MUST-EMIG’s faculty advisor for suitability. Members of MUST-EMIG were voluntarily asked to participate in the online survey. Results of the survey were summarized using descriptive statistics and thematic analysis. Results: 49 responses (46.7% response rate) were collected and analyzed. Participants included 29 (59.2%) male and 20 (40.8%) female medical students. The majority of participants were fourth year students 22 (44.9%). 44 (89.8%) students joined MUST-EMIG to learn how to handle medical emergencies, and expressed a desire of at least 6/10 to learn more about emergency medicine after utilizing opportunities provided by MUST-EMIG. Overall, students had a good experience with MUST-EMIG. They reported that our interest group had provided them networking, unique learning, and leadership opportunities. Having an EMIG significantly affects students’ desire to pursue a career in emergency medicine and their perception of the relevance of emergency medicine. Discussion: An EMIG helps develop interest of medical students in emergency medicine. Students passionate about emergency medicine need to be supported to help them preserve and further develop this passion.
Keywords: Emergency medicine; Emergency Medicine Interest Group (EMIG); Medical students; Uganda